Do motor coordination and sleep difficulties predict peer functioning in children and adolescents with attention‐deficit and hyperactivity disorder after accounting for existing ADHD symptomology?. (13th March 2020) - Mancini, Vincent O.; Althorpe, Kathryn E.; Chen, Wai
Abstract : Children with attention‐deficit and hyperactivity disorder (ADHD) are more likely to experience peer problems compared to their non‐ADHD peers, though ADHD‐specific symptoms only partially explain this association. This study examined whether sleep difficulties and motor coordination problems are additional predictors of peer problems in an ADHD population. An ADHD sample of 72 participants aged 6–14 years ( M  = 9.86 years, SD  = 1.79 years) was evaluated for an association of peer problems with measures of motor coordination, sleep difficulties as well as ADHD and comorbidity symptoms. Hierarchical multiple regression analysis (HMRA) was used to test the current study aims. Motor coordination, but not sleep difficulties, predicted additional variance in peer problems after controlling for inattention, hyperactivity/impulsivity, internalizing problems, oppositionality, and conduct problems. Poor motor coordination predicts peer problems beyond ADHD symptoms. Clinicians seeking to improve peer functioning in children with ADHD should also consider motor coordination difficulties in addition to existing treatment strategies. Statement of contribution What is already known Children with attention‐deficit and hyperactivity disorder (ADHD) experience greater peer problems (i.e., making friends, being victimized, participating in play) than their typically developing peers. Previous studies have attributed this association between ADHD and peer problems to the symptoms of ADHD (i.e., inattention and/or hyperactivity) disrupting the typical trajectory of social development. However, quantitative studies have identified that symptoms of ADHD predict only portion of the variance in a child's peer problems – highlighting that there may be other unique factors that contribute to the higher incidence of peer problems typically observed in this population. What this study adds This study tested whether additional theoretically relevant factors could predict levels of peer problems in children with ADHD beyond the primary symptoms of the disorder. Internalizing symptomatology, conduct problems, oppositionality, motor coordination, and sleep difficulties were added to a regression model already including inattention and hyperactivity symptoms. These factors explained 51% of the variability in peer problems. In this sample of 72 ADHD children, the results of the final model highlighted that only motor coordination and conduct problems remained significant predictors of peer problems – highlighting two potentially important target areas for screening and intervention.